2003
DOI: 10.1111/j.1936-4490.2003.tb00311.x
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Banking Mega‐Mergers: Event Study Evidence from the 1998 Failed Mega‐Merger Attempts in Canada

Abstract: We investigate the main benefit(s) of specific banking mega‐mergers, and whether or not we can infer the benefit(s) from event study evidence of stock market reactions to the mega‐mergers. In addressing these questions, we examine the market's reactions to three announcements surrounding the 1998 failed mega‐merger attempts in the Canadian banking industry. From our analysis, we conclude that market power—not scale, scope, or X‐eficiency economies, or access to government safety net subsidies—was the primary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…However, our results are inconsistent with other studies that find mergers in the banking industry (e.g. Baltazar and Santos, 2003;Ryan et al, 2014) and airline industry (e.g. to have resulted in the exercise of market power.…”
Section: Table 44 -Efficiency and Market Power Effects Of Exchange Mcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results are inconsistent with other studies that find mergers in the banking industry (e.g. Baltazar and Santos, 2003;Ryan et al, 2014) and airline industry (e.g. to have resulted in the exercise of market power.…”
Section: Table 44 -Efficiency and Market Power Effects Of Exchange Mcontrasting
confidence: 99%
“…153). Some studies corroborating the market power hypotheses in the banking industry are (i) Prager and Hannan (1998) -who find that participants in substantial horizontal mergers and their local market rivals exhibited greater reductions in deposit interest rates than banks operating only in markets where no such horizontal mergers took place; (ii) Kane (2000) -who finds that shareholders of large-bank acquirers gain value when a target is large and gain even more value when a target is headquartered in the same state (in-state competitor); and, (iii) Baltazar and Santos (2003) -who report that the market's reaction to the failed bank megamerger attempts in Canada is consistent with the Canadian market ascribing market power as the primary benefit of the mergers (not scale, scope or efficiency economies or access to government safety net subsidies). Fraser et al (2011) assess the stock price response of commercial borrowers with loans outstanding at 12 large banks involved in megamergers and report that the wealth effects on these borrowers are highly negative, statistically significant, and economically important.…”
Section: Market Power In the Banking Industrymentioning
confidence: 99%
“…Traditional event study methodology that assumes independent error terms is not appropriate for the current study because industry‐wide reaction to the policy announcement and intra‐industry reactions to clustered firm announcements would introduce correlated error terms. To deal with correlated error terms, we follow Angbazo and Narayanan (1996), Baltazar and Santos (2003), and Schipper and Thompson (1983) and use an augmented version of the market model with dummy variables appended to reflect the occurrence or non‐occurrence of each event: Equation 1 where R˜ it is firm i 's return on day t , i ={1, 2, … , N }, t ={1, 2, … , T }, R˜ mt is market portfolio return proxied by the Russell 2000 Index return on day t (Howe and Jain, 2004), D jk is a dummy variable that takes on the value of 1 on day k ( k = t 1 to t 2 ) of event j ( j =1, 2, … , J ) and 0 otherwise[6]. Among all the coefficients, β ijk is the parameter of interest; it captures the sensitivity of firm i' s return to event j and thus is analogous to the usual AR measure in traditional event study methodologies.…”
Section: Methodsmentioning
confidence: 99%
“…do so in order to lower their costs or generate other efficiencies+ These should create a positive effect on the aggregate profitability of the firms involved in the combination but lower profits for rivals~King, Wilson, & Naseem, 2002!+ Therefore, future research on evaluating M&As in the brewing sector should include the effects of one firm's merger or acquisition on the stock price of its main competitors+ It follows that events affecting one company also affect the other even though the merger has not actually taken place+ Another useful modification would be to assess different modes of M&A transactions~i+e+, friendly versus hostile acquisition, method of payment, domestic versus international, etc+!+ Furthermore, as acquisitions are complicated events, the event windows could be amended through a further step by using a longer window than the common 21-day window~i+e+, Ϫ10, ϩ30 or Ϫ30, ϩ30!+ Because of the complexity of M&As, it takes longer than a few days surrounding the announcement for market participants to correctly determine the extent of the economic implications for the acquiring firm~Baltazar & Santos, 2003;Mueller & Sirower, 2003!+ At the time of announcement, investors will estimate those implications; however, as time passes by and information is released about an acquisition and its performance, investors will revise their initial estimates+ To exemplify this assumption, Carlsberg's acquisition of Holsten should be mentioned+ In the Ϫ10 to ϩ10-window, this deal has indeed seen negative returns but not at a statistically significant level+ In the weeks following the announcement, the shares fell approximately 10%, prompting a clearly negative response from shareholders+ In an event study, review over the last decade, Harrison et al+~2005! found that less than 10% of the event studies published considered returns more than 31 days after the event+ Hence, it is important to consider the relationship between short-term shareholder reactions and long-term outcomes of M&As+ More work on MNCs in the brewing sector could also focus on evaluating the efficiency of various strategies and considering the structural consequences of different internationalization strategies+ Another amendment would be to classify the M&A transactions in the sample according to their specialization or diversification along the geographical lines~Lepetit, Patry, & Rour, 2004!+ For instance, it may be the case that shareholders will react differently to mergers between competitors operating in similar geographical markets than to mergers between companies operating in different geographical markets+ Hence, there are strategic factors that may be used to explain the variation in wealth gains+ This approach is useful to explain why the phenomenon of brewing M&As occurs despite the fact that they do not increase firm value on average+ Finally, it would be particularly helpful in analyzing M&As in the brewing industry to include the target company's abnormal returns+ There is strong empirical evidence in the bulk of event studies to indicate that target firms' shareholders receive significant increases in their stock prices in comparison to the shareholders of bidding firms+…”
Section: Future Researchmentioning
confidence: 99%